Energy And Environment in Urban Regeneration. Studies for a Method of Analysis of Urban Periphery - De Pascali, Paolo; Alberti, Valentina; De Ioris, Daniela; Reginaldi, Michele (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Despite planning of urban regeneration has been theorized from several decades, today activating concrete programs encounters major difficulties. Moreover, the structural nature of economic crisis and the operators tendency to maintaining obsolete models of urban transformation certainly do not help to overcome the stalemate. The article argues, however, that this framework appears to evolve under the influence of some external factors that bring to the fore the importance of the energy - environmental components in the renewal of the existing city. This address, focused on the concept of urban environment, seems to identify new principles of economic environmental sustainability of the city that converge towards social models of smart community and urban models of smart city. The article then describes the research in progress regarding an operative method to define explicit and replicable bases of the urban environment concept to be considered in plans of urban renewal. Main fields of observation and measurement are “urban comfort” and “anthropogenic load (pollution)”. An experimental application of the analysis is developed on the eastern area of Rome. Finally, the paper offers specific lines for the research development.